(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Congenital toxoplasmosis is a complex infectious-pathological condition caused by the vertical transmission of the Toxoplasma gondii parasite from mother to fetus, characterized by significant morphofunctional alterations and long-term complications during the perinatal period. This article provides an in-depth analysis of the pathogenesis of toxoplasmosis, with particular emphasis on the mechanisms by which the parasite crosses the fetoplacental barrier, its interaction with the immune system, and its tropism for fetal tissues. Primary maternal infection represents the highest risk factor for fetal involvement, with clinical outcomes varying depending on the gestational stage: early infection may result in spontaneous abortion or severe developmental anomalies, while later stages are often associated with subclinical progression followed by delayed neurological and ophthalmological complications. The parasite’s tropism for the central nervous system contributes to the development of the classical triad, including hydrocephalus, intracranial calcifications, and chorioretinitis. Furthermore, immunopathological processes, inflammatory mediators, and intracellular persistence of the parasite play a critical role in disrupting normal fetal development. The article also highlights the importance of modern diagnostic approaches, including serological markers and molecular genetic testing, as well as the effectiveness of early detection and preventive treatment strategies. Prevention of congenital toxoplasmosis relies on screening of pregnant women, enhancement of hygienic measures, and identification of high-risk groups [1,2].